Obtención de péptidos con actividad antihipertensiva in vitro a partir de un subproducto bovino. - Chamorro, Verónica Celeste; Martinez, Fernanda Gabriela; Pazos, Adriana Alejandra; Szerman, Natalia; Ambrosi, Vanina A. (Asociación Argentina de Tecnólogos Alimentarios, 2020)
Bovine by-products represent approximately 66% the weight of the animal. In recent years, the market for these products has decreased because of their low costs. Due to the high protein content, some of these products can be used as substrates of enzymatic hydrolysis to obtain peptides with biological activity. The objective of this work is to obtain bioactive peptides with antihypertensive activity from bovine lung by enzymatic hydrolysis with Alcalase 2.4L® / Flavourzyme® (Novozymes). All the hydrolysates showed antihypertensive activity, inhibiting the action of the angiotensin-converting enzyme (ACE) in values greater than 80%. These findings are interesting because it is possible to increase the value of a meat by-product.